COMPUTATIONAL FLUID DYNAMICS ANALYSIS OF A DOUBLE PIPE HEAT EXCHANGER: MODELLING AND EXPERIMENTAL VALIDATION - Thanh, Trinh Hoai; Nga, Tran Thi To (HUIT Journal of Science, 2023)
Concentric tubes (dual pipe), shell and tube, and plate heat exchangers are the most popular heat transfer devices. It has been used in various food processes such as sterilization, pasteurization, cooling, etc. In this paper, a Computational Fluid Dynamics (CFD) model of a double pipe heat exchanger was set up using the finite element method (FEM) to analyze the fluid characteristic inside the heat exchange. The model of the heat exchanger was built by coupling two major transport equations for fluid flow and energy at a steady-state, i.e., a k-epsilon turbulence model for the turbulence flow and energy transport equation for heat transfer. According to the results, the experimental data and prediction from the simulation are similar for the tube side. However, the experimental data was different from the prediction for outlet temperature at the shell side due to the heat loss from the shell to the outer environment which did not take into account in the model.